Reproducibility of Angle Metrics Using the Time-Domain Anterior Segment Optical Coherence Tomography: Intra-Observer and Inter-Observer Variability. (20th June 2014) - Maram, Jyotsna; Pan, Xiaojing; Sadda, Srinivas; Francis, Brian; Marion, Kenneth; Chopra, Vikas
Abstract: Purpose : To evaluate the reproducibility of anterior chamber angle measurements obtained by the Zeiss Visante anterior segment optical coherence tomography (AS-OCT). Methods : Twenty eyes from 20 normal subjects with open anterior chamber angles were studied. The anterior chamber angle was imaged using the Visante AS-OCT. The angle-opening distance (AOD 500, AOD 750), trabercular iris space area (TISA 500, TISA 750) and scleral spur angle (SS angle) at the inferior angle location were measured. All the subjects underwent imaging in a darkened room (1 foot candles measured at the eye). Images were graded in a masked fashion by certified Doheny Image Reading Center graders. For intra-grader reproducibility assessments, images were re-graded by the same grader 1 week later after random sorting of images. For inter-grader assessments, a second masked grader independently reviewed the images. Intraclass correlation coefficients (ICC) were used to assess reproducibility. Results : Inferior angle measurements of AOD (500, 750), TISA (500, 750) and SS angle for 20 normal eyes were calculated. The intra-observer ICC calculations showed excellent reproducibility for all measurements (AOD 500 = 0.95, AOD 750 = 0.97, TISA 500 = 0.93, TISA 750 = 0.94, SS = 0.96; p < 0.001 for all). The inter-observer ICC calculations showed lower reproducibility for all measurements (AOD 500 = 0.71, p < 0.001; AOD 750 = 0.82, p < 0.001; TISA 500 = 0.49, p = 0.08; TISA 750 = 0.61, p = 0.02; SS = 0.75). Conclusion : Determination of anterior chamber angle measurements was possible with the time-domain AS-OCT, but only modest inter-observer reproducibility was found even among experienced graders.